Rugi Daya Dan Energi Akibat Korona Pada Saluran Udara Tegangan Ekstra Tinggi (SUTET) 500 Kv - Muhamad Haddin; Agil Bahtiar (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2017)
The use of extra high voltage in electrical power transmission system causing corona. A visual corona phenomenon shown by the appearance of visible light radiation, hissing noise, ozone formation and power losses. The impact of corona affect the environment surrounding the overhead line transmission and power losses in the line. This research discusses power and energy losses due to corona by using quantitative method. Calculations performed by calculating relative air density values, disruptive critical voltages, power losses and corona energy. The research object was taken by extra high voltage overhead line transmission 500kV Tanjung Jati B Power Plant to Ungaran Substation.The result show that corona power losses are 0.41-0.44 kW/mil (0.25-0.27kw/km) per phase, with total 1.25-1.30kW/mil (0.78-0.81k/w/km). corona power losses 107.57-112.08 kW along of line. Average of corona energy losses obtained 2642.67 kWh. The percentage of corona power losses to electrical power supplied is between 0.005% to 0.011%.